EVALUASI PELAKSANAAN PROGRAM PEMBERIAN BANTUAN SUBSIDI BENIH DALAM PENINGKATAN PRODUKTIVITAS PADI DI KECAMATAN TORUE KABUPATEN PARIGI MOUTONG - Elis, Elis (Katalogis, 2015)
This research aims to describe how the implementation of Seeds Subsidy Grant Program in Increasing of Paddy Productivity in Torue Sub-district. Parigi Moutong Regency. The research employs descriptive qualitative method with data collection covering observation. There are 6 informants as the sample who selected through purposive sampling. The research result indicates that the implementation of seeds Subsidy6 Grant Program in increasing of Paddy Productivity in Torue Sub-district, Parigi Moutong Regency with model evaluation approach by Bardach namely efficiency and effectiveness of policy not optimal yet. There are some factors influencing, sush as: 1). From technical feasibility, the lateness in distributing and seeds volume given in not appropriate 2). From economy factor it has increased productivity but still not significant felt by farmers, 3). From political aspect, have not been implemented optimally from the aspect of socialization and coaching, and supervision, 4). From administration operation, the operators of program have got commitment and ability organizationally